2014
DOI: 10.1097/mib.0000000000000035
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal Toll-like Receptor 3-dependent Synthesis of Complement Factor B and Systemic Complement Activation in Inflammatory Bowel Disease

Abstract: Abstract:Background: Recent studies link Toll-like receptor 3 (TLR3) to the pathogenesis of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 38 publications
5
26
1
Order By: Relevance
“…TLR3 activation stimulates IL-8 release in HT-29 cells [32] in a nucleotide dependent manner (manuscript in preparation). In addition, TLR3 was found to be involved in different cancers [53, 54] and was also reported to affect intestinal inflammation in a complex manner depending on the conditions, either protecting from inflammation or causing epithelial destruction [5559]. …”
Section: Resultsmentioning
confidence: 99%
“…TLR3 activation stimulates IL-8 release in HT-29 cells [32] in a nucleotide dependent manner (manuscript in preparation). In addition, TLR3 was found to be involved in different cancers [53, 54] and was also reported to affect intestinal inflammation in a complex manner depending on the conditions, either protecting from inflammation or causing epithelial destruction [5559]. …”
Section: Resultsmentioning
confidence: 99%
“…C3aR, C5aR1, and CR3) regulate TLR‐dependent responses, such as those induced by LPS . Reciprocally, TLR activation induces the expression of complement components, thereby potentially contributing to enhance complement activity in an inflammatory environment . For example, LPS induces robust production and release of factor B of the alternative pathway in macrophages (a major source of extrahepatic complement synthesis) through a TLR4‐TRIF pathway that leads to JNK and NF‐κB activation .…”
Section: Tlr Regulation Of Expression Of Complement Componentsmentioning
confidence: 99%
“…The same study showed that the double‐stranded RNA analog polyI:C (a typical TLR3 agonist) also stimulates factor B production in macrophages via a JNK‐ and NF‐κB‐dependent mechanism; however, this pathway was not mediated by TLR3, suggesting the involvement of alternative receptors for polyI:C, such as the cytosolic sensors MDA‐5 and RIG‐I . An independent study showed that polyI:C induces factor B expression also in colonic epithelial cells, albeit via a TLR3‐dependent mechanism . Importantly, the expression of factor B mRNA and protein is significantly enhanced in colonic biopsies of patients with ulcerative colitis and Crohn's disease as compared to healthy controls .…”
Section: Tlr Regulation Of Expression Of Complement Componentsmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Variations within CFB have been previously associated with age-related macular degeneration 18 and atypical hemolytic uremic syndrome, 19 suggesting its potential role in inflammatory disorders. A recent study 20 showed overexpression of CFB mRNA in inflamed versus normal colonic mucosa of IBD patients, suggesting its role in IBD pathogenesis by inappropriate activation of the complement system, contributing to chronic inflammation, one of the hallmarks of UC. This confirms the role of CFB in UC etiology and further supports our novel GWAS findings.…”
Section: Introductionmentioning
confidence: 99%